2021
DOI: 10.1021/jasms.1c00179
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Carbohydrate–Metal Adducts from Solvent Mixtures during Electrospray: A Molecular Dynamics and ESI-MS Study

Abstract: Electrospray ionization (ESI) is frequently used to produce gas-phase ions for mass spectrometry (MS)-based techniques. The composition of solvents used in ESI-MS is often manipulated to enhance analyte ionization, including for carbohydrates. Moreover, to characterize analyte structures, ESI has been coupled to hydrogen/deuterium exchange, ion mobility, and tandem MS. Therefore, it is important to understand how solvent composition affects the structure of carbohydrates during and after ESI. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…The longer acyl chains showed higher signal intensity across all parameters investigated. This may be due to different interactions between analytes and the ionizing modifiers affecting the ionization mechanism and the corresponding MS detection sensitivity. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer acyl chains showed higher signal intensity across all parameters investigated. This may be due to different interactions between analytes and the ionizing modifiers affecting the ionization mechanism and the corresponding MS detection sensitivity. , …”
Section: Resultsmentioning
confidence: 99%
“…This may be due to different interactions between analytes and the ionizing modifiers affecting the ionization mechanism and the corresponding MS detection sensitivity. 46,47 nSF Optimization. The robustness of the system was evaluated by comparing analyte signal intensity and the nESI current to changes in linear flow rate, spray voltage, and solvent composition.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…(Frc, Glc > M7, βCD), (ii) the fructan is more efficiently ionized than the maltose (Frc > Glc; F5 > M5), whereas (iii) a cyclic maltose is more efficiently ionized than its linear equivalent (βCD > M7). Recently, Gallagher and collaborators 34 have provided further insight into the molecular interactions that govern the formation of [Carb + Na] + adduct ions from solvent mixtures during ESI using computational methods and ESI-MS experiments. Interestingly, they concluded that solvent mixtures with 25% or larger proportions of water in methanol are best for ESI-MS experiments.…”
Section: Resultsmentioning
confidence: 99%
“…63 The nSF system showed fewer adducts, which may be due to the low methanol percentage in the droplet, less organic interferent counterions, and other alkali metal adducts. 14,64 The system provides enhanced sensitivity, especially in complex matrices. 65 The efficient nSF desolvation using 90:10 sCO 2 :CH 3 OH with 0.01% formic acid may have provided better ionization, desolvation, and ionic transmission and a small number of adduct peaks.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%